UNDERSTANDING BILINGUAL LEXICOGRAPHY: ITS DEFINITION, SCOPE, AND EVOLUTION («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
The article outlines the history of bilingual lexicography, from its roots in ancient manuscript writing to its current form.  It provides an in-depth overview of the tools and techniques used to create bilingual dictionaries, and outlines the key considerations for developing a bilingual dictionary.
Keywords: Bilingual lexicography, cross-linguistic communication, semantic equivalency, lexical entry selection, historical evolution, practical applications, methodological considerations